Evaluasi Komposisi dan Gizi Bubur Pedas di Kota Pontianak - Tanjung, Safrina Arsi Sekar; Purwayanti, Sulvi; Lestari, Oke Anandika (Jurnal Sains Pertanian Equator, 2017)
This study aims to determine the composition and nutritional value of spicy porridge in Pontianak. This study used qualitative method by surveying and simple random sampling. Samples were taken from spicy porridge stall on five subdistrict of Pontianak which the stall criteria are produce the porridge by itself and the location at main street of each own subdistrict. The research conducted by interviewing the stall owner using questionnaire, recording and weighing all materials that used to produce spicy porridge. The observed variable are proximate analysis and crude fiber. Data were analyzed descriptively. The survey results showed that the ingredient type percentage used to produce spicy porrige at Pontianak are vegetables (51,43%), cereals (19,17%), spices (15,66%), and tubers (10,34%) respectively, while another used ingredients are less than 5%. The results of nutrition percentage are 70,61 % of water, carbohydrate 19,50 %, 6,29 % of fat, 1,65 % of protein, 1,38 % of crude fiber, and 0,57 % of ash.